(untitled) (Annals of Medical Research, 2023)
Aim: We aimed to evaluate the sensitivity of MRI in endometrial cancer by comparing the rate of myometrial invasion of preoperative MRI with the myometrial invasion rates of postoperative histopathological assessment. Materials and Methods: This retrospective study analyzed the medical records of 32 patients diagnosed with endometrial cancer in our hospital’s obstetrics and gynecology clinic from January 2000 to August 2017. Baseline clinical characteristics such as age, gravidity, parity, comorbidities as well as MRI and pathology results were recorded and analyzed. Results: The patients with endometrial cancer had a median age of 57 (36-79) years. Our findings revealed that MRI demonstrated an accuracy of %75 for myometrial invasion with 96% sensitivity, 66% specificity, 96% positive predictive value, and 66% negative predictive value. Conclusion: Overall, the current results supports that the accuracy of MRI for the determination of severity of myometrial invasion in patients with endometrial cancer is the highest when the myometrial invasion is superficial in histopathological examination; however, its accuracy is somewhat lower when there is no or deep myometrial invasion in histopathological examination.